Membrane fatty acid levels as a predictor of treatment response in chronic schizophrenia - Sumiyoshi, Tomiki; Higuchi, Yuko; Matsui, Mie; Itoh, Hiroko; Uehara, Takashi; Itoh, Toru; Arai, Hirofumi; Takamiya, Chieko; Suzuki, Michio; Kurachi, Masayoshi (Psychiatry research, 2011)
Abnormal fatty acid composition in neural membranes, that is, the balance between essential polyunsaturated fatty acids (EPUFAs) and saturated fatty acids, has been suggested to be related to the psychotic symptoms and cognitive impairment of schizophrenia. This study was conducted to test the hypothesis that the ability of atypical antipsychotic drugs to ameliorate positive symptoms and cognitive function relevant to daily living would be predicted by baseline EPUFAs concentrations in the erythrocyte membrane in subjects with schizophrenia. A total of 24 actively psychotic patients with schizophrenia participated in the study. After blood drawing, they were treated with olanzapine or perospirone. The Scale for the Assessment of Positive Symptoms (SAPS) and the Scale for Assessment of Negative symptoms (SANS), as well as the script tasks, a measure of event schema recognition, were administered at baseline and 3 months after the start of treatment. Erythrocyte membrane fatty acid levels were analysed using a gas chromatography system. Scores of SAPS and SANS, as well as script task performance, were improved during treatment with either antipsychotic drug. Regression analysis indicates baseline EPUFAs concentrations were positively and negatively related with percent improvement of positive symptoms and script task performance, respectively. The results of this study suggest composition of phospholipids in the erythrocyte membrane provide a feasible marker to predict treatment response in patients with schizophrenia.